2017
DOI: 10.1080/00952990.2017.1407328
|View full text |Cite
|
Sign up to set email alerts
|

Drug use patterns and predictors among homeless youth: Results of an ecological momentary assessment

Abstract: Background. Alcohol and drug use is associated with significant morbidity and mortality and is highly prevalent among homeless youth. Ecological Momentary Assessments (EMA) have been used to examine the effect of urges on drug use, though not among homeless youth. Objectives. We assessed the patterns of drug use and the correlation between real-time contextual factors and drug use using EMA collected daily. We identified predictors of drug use among a sample of homeless youth 18-25 years old in Houston, Texas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 37 publications
1
30
1
Order By: Relevance
“…Despite frequent alcohol and drug use of homeless persons have been already observed in Brazil and worldwide [20,26,82,83] and with higher infection risk to HIV and T. gondii in general population studies [41,84,85], there was no statistical association observed in the present study. Although one HIV-positive homeless person herein with multiple infections also declared himself as alcohol, marijuana, and skunk cannabis user, the other HIV-positive homeless persons denied alcohol and drug use.…”
Section: Discussioncontrasting
confidence: 71%
“…Despite frequent alcohol and drug use of homeless persons have been already observed in Brazil and worldwide [20,26,82,83] and with higher infection risk to HIV and T. gondii in general population studies [41,84,85], there was no statistical association observed in the present study. Although one HIV-positive homeless person herein with multiple infections also declared himself as alcohol, marijuana, and skunk cannabis user, the other HIV-positive homeless persons denied alcohol and drug use.…”
Section: Discussioncontrasting
confidence: 71%
“…GEMA is considered the gold standard for capturing valid intensive longitudinal self-report information that is embedded in important contextual factors and can be used to understand and predict health risk behaviors [15-19]. The conceptual model for this study (see Figure 1) is based on prior research, showing that within-day variation in various psychosocial characteristics (eg, mood and substance use craving) affects both drug use and sexually risky behavior [20-25]. We hypothesize that access to housing for individuals experiencing homelessness will affect where, when, and with whom they spend time daily [26-28].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study to use longitudinal data and techniques from data science to explore patterns of sheltering and to predict the likelihood of utilizing a shelter or unstable housing among a high-risk, hard-to-reach, population of youth experiencing homelessness. The longitudinal and applied machine-learning methodologies used here are potentially applicable to other hard-to-reach populations and have been used to predict other risk behaviors such as sexual activity and substance use that vary across days, occur with frequency and are potentially affected by real-time factors [ 20 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Invitations to participate were given to YEH who met the inclusion criteria, including having a LH or UH sheltering status, age between 18–24 years (thus meeting the state age of majority), English-speaking and a minimum 6th grade English reading comprehension level (as measured by scores ≥ 4 on the rapid estimate of adult literacy in medicine-short form) [ 37 , 38 ]. Reporting of sampling strategies, measures, schedule, technology used, administration, participant prompting strategy, response rate and compliance rate according to the adapted strengthening the reporting of observational studies in epidemiology checklist for reporting EMA studies [ 39 ] is done elsewhere [ 40 ]. Two respondents did not meet the criteria based on age, and no participants were deemed ineligible from the literacy test.…”
Section: Methodsmentioning
confidence: 99%